2022
DOI: 10.1021/acscatal.2c01213
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Binuclear CuII Sites in the Reduction Half-Cycle of Low-Temperature NH3–SCR over Cu-CHA Catalysts

Abstract: As the state-of-the-art catalyst for the selective catalytic reduction (SCR) of NOx from lean-burn engines, Cu-exchanged chabazite zeolite (Cu-CHA) has been a spotlight in environmental catalysis because of its preeminence in DeNOx performance and hydrothermal stability. The microscopic cycling of active Cu cations between CuII and CuI in response to dynamic, macroscopic reaction conditions dominates SCR catalysis over Cu-CHA zeolites. In such cycling, Cu cations are solvated by gas-phase reactants, e.g., NH3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 80 publications
(279 reference statements)
4
46
1
Order By: Relevance
“…It is well established that the standard SCR mechanism is based on the Cu II → Cu I step (RHC) and the Cu I → Cu II step (OHC). 17 In our previous DFT study, 36 we showed multistep pathway for the OHC with O 2 as the sole oxidant with DFTcalculated activation energies (E a ) of 99−110 kJ/mol (reaction 1 in Table 1). In this study, the E a values of possible reactions during the initial stage of RHC (reactions 2−11 in Table 1) were calculated and compared.…”
Section: O 2 -Free Oxidation Of No By Cu II Species At 30 °Cmentioning
confidence: 92%
See 1 more Smart Citation
“…It is well established that the standard SCR mechanism is based on the Cu II → Cu I step (RHC) and the Cu I → Cu II step (OHC). 17 In our previous DFT study, 36 we showed multistep pathway for the OHC with O 2 as the sole oxidant with DFTcalculated activation energies (E a ) of 99−110 kJ/mol (reaction 1 in Table 1). In this study, the E a values of possible reactions during the initial stage of RHC (reactions 2−11 in Table 1) were calculated and compared.…”
Section: O 2 -Free Oxidation Of No By Cu II Species At 30 °Cmentioning
confidence: 92%
“…5,8−16 It is well established that the standard SCR mechanism is based on the Cu II /Cu I redox cycles; the Cu II → Cu I step so-called reduction half-cycle (RHC) and the Cu I → Cu II step so-called oxidation half-cycle (OHC). 8,17 Assuming an OH − -coordinated Cu 2+ cation at zeolite oxygen (O Z − ) as an active site of Cu-zeolite catalysts, the Cu II → Cu I step (RHC) is described as…”
Section: Introductionmentioning
confidence: 99%
“…56,57 More recently, mobile [Cu 2+ (OH)(NH 3 ) x ] + complexes formed by NH 3 solvation of ZCu 2+ OH ions (stabilized by one framework negative charge), have been proposed to be relevant in the reduction half-cycle, as discussed in mode detail in Section 3. 58,59 Finally, the formation and separation of Cu pairs assisted by NH 3 solvation is the core of one of the recently proposed mechanisms for NH 3 -SCR, which includes the role of Brønsted sites to facilitate the decomposition to N 2 and H 2 O of HONO and H 2 NNO intermediates formed on Cu sites (Fig. 1, right panel, part a).…”
Section: Redox Reaction By Cu Zeolitesmentioning
confidence: 97%
“…As mentioned above, the role of NH 3 in solvating and mobilizing Cu + and Cu 2+ ions in the low temperature NH 3 -SCR reaction has been proposed to be pivotal, in both the oxidation and reduction half-cycles. 3,52,58,59 The ability of NH 3 to solvate the cations, replacing framework oxygen atoms (O fw ) from their rst-shell coordination sphere has been proven by X-ray absorption and emission spectroscopies (XAS and XES). 50,51 More in detail, Extended X-ray Absorption Fine structure (EXAFS) showed the disappearance of the ngerprint for framework coordinated Cu-sites (second-shell peak at $2.3 A in the phase-uncorrected modulus of FT-EXAFS spectrum) when a Cu-CHA catalysts was contacted with the NH 3 -SCR reactants below 250 C. This was accompanied by a raise in the pre-edge peak at $8982.5 eV, deriving from 1s / 4p transition in the linear Cu + (NH 3 ) 2 complex in the corresponding X-ray absorption near edge structure (XANES) spectrum, and by modications in the XES spectra compatible with the substitution of O fw ligand with N atoms from the NH 3 molecule (Fig.…”
Section: Cu Mobility: Relation With Oxidation State and Ligands Coord...mentioning
confidence: 99%
“…The detailed reaction mechanism is still under debate, indicating the complexity of both RHC and OHC. 157 …”
Section: Reaction Mechanismsmentioning
confidence: 99%